PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN SUPERVISI AKADEMIK TERHADAP KINERJA GURU UNTUK MENINGKATKAN MUTU PENDIDIKAN SEKOLAH DASAR DI KECAMATAN PULOMERAK - Iriyanah, Iriyanah; Sutisna; Komarudin, Mamay (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The role of the school head as an internal educational institution leader is the impetus for this thesis, as is the importance of effective leadership within the school's environment for fostering a positive school climate, boosting teacher morale and productivity, and building a strong foundation for student achievement. Quality human beings are in high demand due to the increasing level of competition in today's world, and education is the key to achieving this goal. An improved standard of living is directly proportional to a high quality educational system. For the purpose of research. Here are five things to keep in mind: 1) how school leadership affects teacher performance, 2) how academic supervision affects teacher performance, 3) how teacher performance affects education quality, 4) how school leadership affects education quality, and 5) how academic supervision affects classroom quality. Research the In the District of Pulomerak, this became the educational foundation. We addressed the issue by using a quantitative approach with a correlational strategy. Research the The purpose of this is to determine if there is a relationship between various aspects of a real-world phenomenon.Data analysis, data collection, data reduction, presentation, and conclusion drawing follow data collection. In Pulomerak District, studies have shown that strong leadership at the school level and strong academic supervision have a positive effect on teacher performance and the overall quality of education provided by the district's schools.